2006
DOI: 10.1002/chem.200600562
|View full text |Cite
|
Sign up to set email alerts
|

Iridium(III) Silyl Alkyl and Iridacyclic Compounds Supported by 4,4′‐Di‐tert‐butyl‐2,2′‐bipyridyl

Abstract: Treatment of IrCl(3)x H(2)O with one equivalent of 4,4'-di-tert-butyl-2,2'-bipyridyl (dtbpy) in N,N-dimethylformamide (dmf) afforded [IrCl(3)(dmf)(dtbpy)] (1). Alkylation of 1 with Me(3)SiCH(2)MgCl resulted in C--Si cleavage of the Me(3)SiCH(2) group and formation of the Ir(III) silyl dialkyl compound [Ir(CH(2)SiMe(3))(dtbpy)(Me)(SiMe(3))] (2), which reacted with tBuNC to afford [Ir(tBuNC)(CH(2)SiMe(3))(dtbpy)(Me)(SiMe(3))] ([2(tBuNC)]). Reaction of 2 with phenylacetylene afforded dimeric [{Ir(C[triple chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 79 publications
6
25
0
Order By: Relevance
“…). [6] Thus, it seems reasonable to assume that the Ag I oxidation of 8 resulted in a transient Ir III -thiyl radical cation species that dimerized by formation of an S-S disulfide bond.…”
Section: Iridacyclic Thiolate Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…). [6] Thus, it seems reasonable to assume that the Ag I oxidation of 8 resulted in a transient Ir III -thiyl radical cation species that dimerized by formation of an S-S disulfide bond.…”
Section: Iridacyclic Thiolate Complexesmentioning
confidence: 99%
“…Few stable Ir IV alkyls and aryls have been isolated, [4,5] presumably because of the stability of low-spin d 6 Ir III compounds, which renders their oxidation difficult. Recently, we synthesized the irida(III)cycle [Ir(dtbpy){CH 2 CMe 2 -C c 6 H 4 (Ir-C c )}(C 6 H 4 tBu-2)] (dtbpy = 4,4Ј-di-tert-butyl-2,2Ј-bipyridyl) (1) by alkylation of [Ir(dtbpy)Cl 3 (dmf)] (dmf = N,N-dimethylformamide) with PhMe 2 CCH 2 MgCl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction of complex 2 with 2-phenylpyridine resulted in cyclometalation of 2-phenylpyridine, whereas that with 4-(2-pyridyl)benzaldehyde led to decarbonylation of the formyl group. Cationic Ir and Rh alkyl complexes 7 and 8 containing the noncoordinating [4] and NaBAr [19] were synthesized as described elsewhere. Atom labeling schemes for the metallacycles in cyclometalated complexes and the ppyH and dtbpy ligands are shown below.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] We found that the alkylation of [Rh(dtbpy)-Cl 3 (dmf)] (dmf = N,N-dimethylformamide) with Me 2 CCH 2 PhMgCl afforded the neophyl complex [Rh(dtbpy)(κ 2 -C,CЈ-CH 2 CMe 2 C 6 H 4 )(CH 2 CMe 2 Ph)]…”
Section: Introductionmentioning
confidence: 99%